Molecular diagnosis and genotyping of Orientia tsutsugamushi in Maesot and Chiangrai, Thailand - Rungrojn, Artharee; Batty, Elizabeth M.; Perrone, Carlo; Abdad, Mohammad Yazid; Wangrangsimakul, Tri; Brummaier, Tobias; McGready, Rose; Day, Nicholas P. J.; Blacksell, Stuart D. (Frontiers in Tropical Diseases, 2023)
Scrub typhus is a neglected tropical disease with an estimated 1 million cases annually. The Asia-Pacific region is an endemic area for scrub typhus, especially in Thailand. Between June 2018 to December 2019, 31 patients with acute undifferentiated febrile illness (AUFI) were recruited as part of clinical trials and tested positive by a scrub typhus IgM RDT. Of the 17 buffy coat patient samples tested by 47kDa real-time PCR and 56kDa type-specific antigen (TSA) nested PCR, 94% (16/17) were positive, and of the 11 patients that presented with eschar lesions, 100% (11/11) of the eschar samples were confirmed positive. Genetic analysis of the 560 bp partial 56-kDa TSA gene demonstrated that most Orientia tsutsugamushi (Ot) infections were with Karp, Gilliam, Taiwan, P23, and CM606-like strains. This is the second occasion that the CM606-like and P23-like strains were reported in northern Thailand (first reported in 2011 and 2013, respectively). This study demonstrates that 1) the eschar remains the most reliable biological sample for PCR diagnosis of scrub typhus and 2) Northwestern Thailand has significant diversity of Ot strains which under-lines the requirement for ongoing surveillance to increase our understanding of Ot diversity to ensure accurate diagnostics and treatment.